THE FUNCTIONAL ROLE OF NON-GOVERNMENTAL AND PUBLIC ORGANIZATIONS IN THE SOCIAL PROTECTION SYSTEM - Mirzayev Sherali Maxmatqulovich (Bright Mind Publishing, 2026)
This article provides a comprehensive analysis of the functional role of non-governmental and public organizations in the social protection system. It examines the theoretical foundations of social protection, the mechanisms of cooperation between the state and civil society institutions, and the main areas of activity of non-governmental organizations. Based on both national and international experience, the study analyzes the effectiveness of these organizations in supporting socially vulnerable groups, identifies existing challenges, and discusses prospects for improving social services. The findings are of practical significance for enhancing social policy, strengthening social partnerships, and ensuring targeted support for populations in need.
Keywords: Social protection, non-governmental organizations, public organizations, civil society, social partnership, social services, social policy.